Male Accessory Glands Infections: Mechanisms of Influence on Male Fertility - I. V. Vinogradov; A. R. Zhivulko; S. V. Korolev (Вестник урологии, 2020)
Male accessory glands infections (MAGI) are considered one of the causes of male infertility. Chronic prostatitis is the most prevalent form of MAGI. Researches that assessed the influence of chronic prostatitis on conventional semen parameters have shown contradictory results, so the debate regarding this issue continues. Conventional semen parameters are imperfect markers of male fertility, as many men remain infertile despite being normozoospermic. The search for reliable predictors of male fertility continues to this day. Oxidative stress is considered one of the main pathogenetic mechanisms of male infertility. Free radical oxidation is the leading cause of spermatozoa DNA damage. Spermatozoa DNA fragmentation caused by oxidative stress was associated with a number of unsuccessful reproductive outcomes. There are several factors that are responsible for making spermatozoa vulnerable to free radical damage including abnormal maturation characterized by insufficient chromatin protamination. Acrosin activity defines the ability of spermatozoa to penetrate the ovum membrane and is therefore an independent marker of spermatozoa fertilizing capacity. Possible mechanisms of chronic prostatitis influence on male fertility and current scientific data regarding its association with novel predictors of male infertility are discussed in this article.The study did not have sponsorship. The authors have declared no conflicts of interest.